Pengaruh Pemberian Ekstrak Metanol Carica papaya Terhadap Perkembangan, Fertilitas, Dan Fekunditas Spodoptera frugiperda - Padillah, Rifqi; Ramadhan, R. Arif Malik; Firmansyah, Efrin (Jurnal Agro Wiralodra, 2024)
The increasing pattern of use of synthetic pesticides and the unwise use of synthetic pesticides can cause various further problems such as air, water and soil pollution which will affect the environment and the health of farmers. The papaya plant (Carica papaya L.) belongs to the Caricaceae family which has been widely used in traditional medicines. This research was carried out with the aim of determining the effect of administering C. papaya methanol extract on various biological aspects of Spodoptera frugiperda and to determine the compound content contained in the extract. This research will be carried out from June to August 2022 at the Agrotechnology Laboratory of the Tasikmalaya University of Perjuangan. The design used was a non-factorial Completely Randomized Design (CRD) with 5 treatment levels including 0%, 1%, 2%, 3% and 4% papaya extract. Each treatment was repeated 4 times so that there were 20 experimental units. The results of the study showed that 2% methanol extract of C. papaya leaves had a significant effect on inhibiting the growth of S. frugiperda from instar II to instar III but had no significant effect on the development of larvae from instar IV to imago. The research results showed that the methanol extract of C. papaya was not effective in inhibiting the formation of pupae and imago. Application of C. papaya leaf extract at a concentration of 1% can reduce the fecundity level of female imago of S. frugiperda but does not affect the fertility of the eggs produced.